Organizing, performing and presenting scientific work in engineering education with the help of mobile devices - May, Dominik; Ossenberg, Philipp (International Journal of Interactive Mobile Technologies (iJIM), 2015)
The meaningful use of mobile devices in higher education learning contexts is still underrepresented at German universities. Even if these “new” technologies open up totally new teaching and learning experiences the current use is strongly dominated by simple technology provision. With a special course—designed for engineering students—the authors want to change this and go more into the direction of meaningful interaction and collaboration with the help of mobile devices throughout the learning process. The course is developed to give the students the opportunity to use tablet PCs in context of their studies and simultaneously to improve their ability in the field of scientific working processes. Making use of the online tool Evernote supported this aim. This tool allows users to work out and share digital notebooks and with this to organize as well as document a working process. In this case it was used to support a scientific research process from the beginning to the end. As Evernote can be used with an mobile app it easily can be used on tablet PCs. Hence, it supports the course idea of using mobile devices in perfect way. The course itself is divided into four face-to-face meetings and three working phases. By taking part in the course the students go through their own research project with explicit steps—from having a new idea for research to the results’ presentation. The meetings are mainly used in order to introduce tools or techniques for research processes. During the working phases the students do their research, create presentations, a poster, and a scientific report. Based on the internal course evaluation and the students’ feedback we observed, that the combination of tablet PCs with the Evernote software is a good opportunity to show how mobile devices can be meaningfully integrated into higher engineering education.